Investigation of Fructus sophorae extract’s therapeutic mechanism in atrophic vaginitis based on network pharmacology and experimental validation - Zheng, Jiarui; Wang, Weiming; Song, Wenting; Zhang, Yehao; Yao, Mingjiang; Wang, Guangrui; Huang, Zishan; Li, Feng; Ren, Junguo; Lin, Li; Fan, Xiaodi; Liu, Jianxun (Frontiers in Pharmacology, 2025)
ObjectiveThis study systematically elucidates the therapeutic mechanism of Fructus sophorae extract (FSE) against atrophic vaginitis (AV) by integrating network pharmacology with in vitro experimental validation.MethodsPotential drug targets of FS and AV-related disease targets were systematically retrieved from TCMSP, SWISS Target Prediction, GeneCards, and DisGeNET databases. The putative therapeutic targets of FS against AV were identified through target overlap analysis between drug and disease targets. Functional enrichment analyses of GO terms, KEGG pathways, and disease associations were performed using DAVID database, with results visualized by Cytoscape software. Molecular docking validation and binding affinity visualization between FS components and target proteins were carried out using PubChem database and PyMOL software. The AV animal model was established by bilateral ovariectomy (OVX). To validate FS’s effects on target protein expression, immunohistochemical staining and Western blot analyses were performed.ResultsThrough target intersection analysis between 137 drug targets and 1,777 disease targets, a total of 100 potential therapeutic targets were identified for FS in AV treatment. Subsequent core gene screening revealed key targets, namely, EGFR, AKT1, ESR1, and TNF. GO and KEGG enrichment analyses demonstrated significantly enriched pathways, with the PI3K/AKT signaling pathway showing particular relevance. Molecular docking analysis revealed strong binding affinity between FS components and the functional domains of EGFR, AKT1, and ESR1. An OVX-induced rat AV model was successfully established, with pathological and molecular validation achieved via immunohistochemistry and Western blot analyses. FS treatment significantly normalized the dysregulated expression levels of p-PI3K/PI3K, p-AKT/AKT, ERα, EGF, and EGFR.ConclusionFS demonstrates multi-target regulatory capacity, specifically modulating p-PI3K/PI3K, p-AKT/AKT, ERα, EGF, and EGFR signaling pathways, which substantiates its potential as a promising therapeutic agent for AV. These findings provide mechanistic insights into FS’s therapeutic targets against AV, establishing a theoretical foundation for its translational application in AV therapy.